PERBEDAAN KADAR HEMOGLOBIN MAHASISWI KEDOKTERAN UNLAM YANG MELAKUKAN DAN TIDAK MELAKUKAN SENAM AEROBIK - Ekky Adrianto C.G.; Miftahul Arifin; Husnul Khatimah (Berkala Kedokteran, 2015)
Aerobics is believed becoming a good sport choice especially for women to be spared from lower hemoglobin level risk. This study aims to determine the difference of hemoglobin level between medical female students of Lambung Mangkurat University who did and didn’t do aerobics. This study took 33 female students as subjects who divided to 17 people in control group and 16 people in exercise group. Exercise group did aerobics twice a week for a month. Blood sample were taken twice, before and after a month of study. The result of this study showed descriptively a little decreased average of hemoglobin level in exercise group, from 12,38±0,83 g/dL to 12,37±0,71 g/dL, but statisticly showed insignificant decreased. However, descriptively average of hemoglobin level after did aerobics in exercise group showed a little higher than control group, those are 12,37±0,71 g/dL in exercise group and 12,23±0,86 g/dL in control group, although statisticly showed insignificant difference (p>0,05). In conclusion, there was insignificant difference of hemoglobin level between medical female students who did and didn’t do aerobics for a month. Keywords: hemoglobin level, aerobics, female students